An investigation on the effectiveness of result based management in enhancing quality education service delivery: a case of Matinunura High School - Tirivavi, Osward (Midlands State University, 2015)
The research was undertaken to ascertain the effectiveness of the RBM system in enhancing quality education service delivery. This study was motivated by a decline in public confidence, inconsistent results in terms of pass rate and quality of passes, poor performance in core-curricular activities at Matinunura High School and the institution stands to benefit from the effective implementation of the Result Based Management. The purpose of the study was to ascertain the effectiveness of planning and implementation of RBM to achieve quality education service delivery, determine the effectiveness of administered interventions in the attainment of expected outputs in ensuring quality education service delivery and to establish the key success factors for RBM in attaining quality education service delivery. The literature review was done through inquiry of textbooks, journals, research papers and online sources from different authors on Result Based Management. The researcher used both exploratory and descriptive research designs to carry out the study. The estimated target population was 420 constituting of ordinary level exam classes and upper six students, teachers, administrators at Matinunura as well as education officers where a sample size of 241 was then drawn for this study. Probability and non- probability sampling techniques were employed to draw samples from different targeted groups. The researcher also used questionnaires and interviews to gather primary data of a qualitative and quantitative nature which compelled the researcher to administer quantitative and qualitative approaches of analyzing the gathered data. Secondary data was obtained from the school registers, results analysis, journals and other online sources. It can be noted that the researcher used triangulation of research design, sampling methods, research instruments and data sources to ensure valid and reliability of research results. The researcher were found out that RBM system is difficult to plan and implement as teachers are finding it difficult to translate them into work plans and match resources with the desired results, intervention have not been effective and participation, continuous training and leadership commitment were identified as RBM’s success factors. The researcher therefore recommended that a change management system be put in place for RBM to be understood, strengthen interventions as well as promote participation and training to achieve a buy-in. Leadership commitment to be achieved by “building a strong and exemplary leadership which does walk the talk”.